Functional heartburn has more in common with functional dyspepsia than with non-erosive reflux disease. Issue 9 (20th May 2009) - Savarino, E; Pohl, D; Zentilin, P; Dulbecco, P; Sammito, G; Sconfienza, L; Vigneri, S; Camerini, G; Tutuian, R; Savarino, V
Abstract : Introduction: Functional dyspepsia and non-erosive reflux disease (NERD) are prevalent gastrointestinal conditions with accumulating evidence regarding an overlap between the two. Still, patients with NERD represent a very heterogeneous group and limited data on dyspeptic symptoms in various subgroups of NERD are available. Aim: To evaluate the prevalence of dyspeptic symptoms in patients with NERD subclassified by using 24 h impedance-pH monitoring (MII-pH). Methods: Patients with typical reflux symptoms and normal endoscopy underwent impedance-pH monitoring off proton pump inhibitor treatment. Oesophageal acid exposure time (AET), type of acid and non-acid reflux episodes, and symptom association probability (SAP) were calculated. A validated dyspepsia questionnaire was used to quantify dyspeptic symptoms prior to reflux monitoring. Results: Of 200 patients with NERD (105 female; median age, 48 years), 81 (41%) had an abnormal oesophageal AET (NERD pH-POS), 65 (32%) had normal oesophageal AET and positive SAP for acid and/or non-acid reflux (hypersensitive oesophagus), and 54 (27%) had normal oesophageal AET and negative SAP (functional heartburn). Patients with functional heartburn had more frequent (p<0.01) postprandial fullness, bloating, early satiety and nausea compared to patients with NERD pH-POS and hypersensitive oesophagus. Conclusion: The increased prevalence of dyspeptic symptoms in patients with functional heartburn reinforces the concept that functional gastrointestinal disorders extend beyond the boundaries suggested by the anatomical location of symptoms. This should be regarded as a further argument to test patients with symptoms of gastro-oesophageal reflux disease in order to separate patients with functional heartburn from patients with NERD in whom symptoms are associated with gastro-oesophageal reflux.